Real-world patient characteristics and clinical outcomes in patients with myelofibrosis in Japan - Yusuke Yasutomi; Masashi Takano; Yi-Chen Chen; Chi-Chang Chen; Seok-Won Kim; Catherine McGuiness; Alex Slowley; Keita Kirito (PLoS ONE, 2026)
Anemia is associated with increased morbidity, mortality, healthcare resource utilization, and costs in myelofibrosis. This longitudinal, retrospective, and descriptive cohort study used a Japanese health administrative database (Medical Data Vision) to examine treatment patterns, transfusion burden, healthcare resource utilization, and costs in patients with myelofibrosis and a subset treated with a Janus kinase inhibitor. Ruxolitinib (a Janus kinase inhibitor) was the first targeted therapy for myelofibrosis in Japan (2014). Patients were identified from April 1, 2015 to June 30, 2022. In the overall myelofibrosis cohort, myelofibrosis diagnosis was the index date; in the Janus kinase inhibitor-treated subgroup, the first date of Janus kinase inhibitor use was the index date. Of the 836 patients with myelofibrosis, median age: 73 years at or before index; female: 38.0%; median follow-up: 576 days; anemia: 59.9%; thrombocytopenia: 18.7%. At index, 37.9%, 6.6%, and 55.5% of patients were transfusion-dependent, -requiring, and -independent, respectively. Median overall survival from myelofibrosis diagnosis was 83.3 months from the index date. Of 281 patients who received a Janus kinase inhibitor, median age: 74 years at or before index; female: 39.5%; median follow-up: 592 days; anemia: 66.9%; thrombocytopenia: 22.8%. All patients who received a JAK inhibitor were treated with ruxolitinib; mean dose was 15.6 mg/day and median duration of treatment was 14 months. The proportion of patients who were transfusion-dependent, -requiring, and -independent in this subgroup was 47.0%, 9.3%, and 43.8%, respectively. Median overall survival from myelofibrosis diagnosis was 53.9 months from first Janus kinase inhibitor administration. This real-world study showed the clinical characteristics and outcomes of Japanese patients with myelofibrosis.